In vitro comparison of the effectiveness of various antimicrobial locks with taurolidine in the treatment and prevention of catheter-related bloodstream infections in patients receiving parenteral nutrition - Visek, Jakub; Ryskova, Lenka; Machacova, Alena; Marikova, Martina; Blaha, Vladimir (Nutrition, 2023)
OBJECTIVES: To evaluate the effectiveness of various taurolidine solutions in the prevention and treatment of catheter-related bloodstream infections (CRBSIs) caused by the entire spectrum of microbes in patients receiving parenteral nutrition in a shorter period of time. METHODS: The in vitro method was used to test for eradication of biofilm. Different locks were used: TauroSept (2%), TauroLock (1.35%), TauroLock half concentration, and 3.5% taurolidine and tested on Staphylococcus (S.) epidermidis, S. aureus, S. hominis, methicillin-resistant S. aureus (MRSA), Pseudomonas (P.) aeruginosa (PSAE), multidrug-resistant P. aeruginosa (MR PSAE), vancomycin-resistant enterococci, Klebsiella pneumoniae producing carbapenemase (KPC), Klebsiella pneumoniae producing extended-spectrum beta-lactamase (KLPN ESBL), Candida (C.) albicans, and C. glabrata. Broviac catheters were incubated for growth of each organism and then incubated in lock solutions. Colony forming units (CFUs) were then counted after 30 min, 60 min, and 120 min of incubation. RESULTS: A statistically significant decrease in CFUs was observed after 30 min of taurolidine exposure for S. hominis, PSAE, KLPN ESBL, KLPN KPC, C. albicans, and C. glabrata; after 60 min of exposure for S. epidermidis, PSAE, MR PSAE, KLPN ESBL, KPC, C. albicans, and C. glabrata; and after 120 min of exposure for S. epidermidis, S. hominis, S. aureus, PSAE, MR PSAE, KLPN ESBL, KPC, C. albicans, C. glabrata. CONCLUSIONS: The application of taurolidine is effective in the treatment of CRBSIs. Taurolidine proved to be more effective against Gram-negative microorganisms during a 30-min exposure. Using 0.675% taurolidine is still effective. To achieve the required antimicrobial effect, the catheter must be sanitized for at least 2 h.
Keywords: sepse; Catheter-Related Infections; Anti-Infective Agents; Parenteral Nutrition; katétrové infekce; Methicillin-Resistant Staphylococcus aureus; antiinfekční látky; Staphylococcus aureus; methicilin rezistentní Staphylococcus aureus; parenterální výživa; lidé; Humans; Sepsis; katétry; Catheters